Pengaruh Intellectual Capital Terhadap Nilai Perusahaan - Rizki Amalia Juwandinata; Sari Andayani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze how intellectual capital affects the value of companies. Intellectual capital is one of the intangible assets that has an important role in creating a competitive advantage and improving the company's performance, as well as the company's value. The variables in this study consist of intellectual capital and company value. There are three components in intellectual capital, namely value added capital employed (VACA), value Added human capital (VAHU), and structural capital value added (STVA). Meanwhile, the value of companies in this study was measured using the Tobin,s Q method. This study uses a quantitative method. The data used is secondary data in the form of annual financial report data for the banking sub-sector listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The data collection technique uses the purposive sampling method and was obtained from 25 companies with a period of 5 years, so 125 sample data were collected. The analysis in this study uses the Smart PLS version 3.0 program which is used to test the relationship between intellectual capital and company value. The results of the study show that intellectual capital has an effect on the value of the company.